Entre portos e ritos: a memória do Candomblé Angola em Santos - Figueiredo, Janaina de (2016)
In this paper I place the memory of the angola candomblé in Santos city, indentifying the caboclo s role in this religious structure. The memories pointed out a fixed point in space, which is the pier. The pier became the scenery, the landscape, in which the memory of a candomblé by the sea was anchored. In the speaker s voices, the masts, the sails, the streetcars, the streets and the city allies have expressed themselves as walking rhetoric and also pieced together the web in which several practices and cultural dynamics were attached. In this net of sense and meaning the angola nation takes a privileged spot in this analysis. We defend that the caboclo is a key component in this religious structure of this nation. This entity brought, as one tries to argue, a kind of unity to the angola candomblé. One of the premises which involves the caboclo s analysis consists in giving him the role to keep angola candomblé memory and identity. This thesis is a paper about the memory in many ways like: the researcher s view, the crossed memories, the memory guardians role, the caboclo s performances, and other aspects